PENGARUH PEMBERIAN EKSTRAK ETANOL BUAH AREN (Arenga pinnata Merr.) TERHADAP KADAR KREATININ, UREUM DAN HISTOLOGI GINJAL TIKUS PUTIH (Rattus norvegicus L.) YANG DIINDUKSI KARBON TETRAKLORIDA (CCl4) - Awaliah Sifa, Nurharija; Febriani, Husnarika; Widiarti, Leni (Universitas Cokroaminoto Palopo, 2025)
One substance that produces radical compounds is carbon tetrachloride (CCl4). As a solvent, insecticide, coolant, stain remover, and soap, carbon tetrachloride is widely used. Direct skin contact, ingestion, inhalation, and eye contact are ways this material enters the body. The antioxidants found in palm fruit (Arenga pinnata Merr.) can help protect against damage caused by free radicals. This study aims to determine how giving ethanol extract of palm fruit (Arenga pinnata Merr.) to white rats (Rattus norvegicus L.) affects creatinine, urea levels and kidney histology when exposed to carbon tetrachloride (CCl4).This study used a completely randomized design with 20 mice divided into 5 treatment groups. Negative controls were given food, drink and 1 ml/kg BW olive oil, positive controls were given 1 ml/kg BW carbon tetrachloride and olive oil with a ratio of 1:3. Treatments 1, 2 and 3 were given carbon tetrachloride 1ml/kg BW and olive oil with a ratio of 1:3 and given ethanol extract of palm fruit at different doses (P1= 90 mg/kg BW, P2= 180 mg/kg BW, P3= 360 mg/kg BW) for 16 days. The results obtained include that ethanol extract of palm fruit has a very significant effect on creatinine, urea and kidney histology. The optimal dose of palm fruit ethanol extract to improve kidney is a 360 mg/kg BW.